American Indian and Euro-Western negotiations: Creating mutual benefit with upsurging antenarrative spirals. (December 2016) - Rosile, Grace Ann; Herder, Richard; Boardman, Calvin M
Antenarrative (before-the-narrative) analysis reveals features of historical Native American and Euro-Western negotiations which contributed to undesired and unintended outcomes, while sometimes overlooking the resplendent possibilities of living stories. This study uncovers the antenarrative processes in existing accounts of three particular indigenous cultures negotiating with Euro-Westerners. These three case examples include two negotiations that were partial victories accompanied by lingering resentments, and one success. In the latter, participants were able to use elements of living story to break an impasse and achieve lasting success based on mutually beneficial outcomes. Breaking out of restrictive linear and cyclical antenarratives, and instead incorporating spiral and rhizomatic ones, opens more options for negotiators. Power-equal perspectives, along with the diversity-accommodating nature of rhizomatic (decentered and networked) ways of telling stories, can help negotiating parties to co-create upsurging spirals of win–win stories for mutual benefit.